Application of mobile agent itinerary planning based on data offloading strategy of energy optimal method - Xiaobo SHI; Jianyu LU; Wenye WANG; Hang RUAN; Xuan ZHU (Dianxin kexue)
A data offloading strategy for optimizing itinerary planning of MA（mobile agent）was proposed. When MA visits source nodes based on data offloading strategy，it decides whether to transfer data package via optimized offloading itinerary and MA（mobile agent）visits data source nodes via conventional itinerary. Based on considerable simulations with the representative MA itinerary planning，i.e. itinerary energy minimum for first-source-selection （IEMF），it verifies that the problem of excessive energy consumption from source nodes can be efficiently solved and the lifetime of source nodes is prolonged.